WETLAND ECOSYSTEMS AND COASTAL HABITAT DIVERSITY IN GUJARAT, INDIA - Oswin D. Stanley (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Wetland ecosystems are the major contributors for the nations’ wildlife biodiversity, productivity and economy. The paper elaborates the habitat diversity of wetlands in Gujarat, India, the floral and faunal diversity of each ecosystem, the major industrial and development pressures posed by the mangroves and coastal ecosystems. Thus indicates the significance and necessity for wetland habitat conservation.